Babies and brains: habituation in infant cognition and functional neuroimaging - Turk-Browne, Nicholas B.; Scholl, Brian J.; Chun, Marvin M. (Frontiers in Human Neuroscience, 2008)
Many prominent studies of infant cognition over the past two decades have relied on the fact that infants habituate to repeated stimuli — i.e. that their looking times tend to decline upon repeated stimulus presentations. This phenomenon had been exploited to reveal a great deal about the minds of preverbal infants. Many prominent studies of the neural bases of adult cognition over the past decade have relied on the fact that brain regions habituate to repeated stimuli — i.e. that the hemodynamic responses observed in fMRI tend to decline upon repeated stimulus presentations. This phenomenon has been exploited to reveal a great deal about the neural mechanisms of perception and cognition. Similarities in the mechanics of these two forms of habituation suggest that it may be useful to relate them to each other. Here we outline this analogy, explore its nuances, and highlight some ways in which the study of habituation in functional neuroimaging could yield novel insights into the nature of habituation in infant cognition — and vice versa.